Effectiveness of Visual-Tactile Mobile Augmented Learning on Breast Self-Examination Knowledge among Women of Reproductive Age in Rokan Hulu, Indonesia (Program Studi Pendidikan Teknologi Infromasi UMK, 2025)
Breast cancer remains the leading cause of cancer-related morbidity and mortality among women in Indonesia, with most cases detected at advanced stages due to limited awareness and practice of early detection methods. Breast self-examination (BSE) is a simple and cost-effective technique recommended for early detection, yet knowledge and practice among women of reproductive age remain low in rural communities. This study aimed to examine the effectiveness of Visual-Tactile Mobile Augmented Learning (MAL) in improving BSE knowledge among women of reproductive age in Rokan Hulu, Indonesia. A quasi-experimental pretest–post-test control group design was conducted with 60 purposively selected participants, divided into an intervention group receiving MAL-based education integrating interactive visual modules and tactile simulations, and a control group receiving conventional education through leaflets and counselling. Knowledge levels were measured using a validated questionnaire, and statistical analysis was performed using paired t-tests and independent t-tests with a significance level of p < 0.05. The results showed a significant improvement in BSE knowledge among participants in the intervention group compared with the control group (mean increase = 2.9 points; p < 0.001; Cohen’s d = 0.85, large effect size). In conclusion, Visual-Tactile MAL is an effective educational innovation for enhancing BSE knowledge, offering promising implications for digital health strategies and community-based breast cancer prevention programs in resource-limited settings.